2020
DOI: 10.18235/0002138
|View full text |Cite
|
Sign up to set email alerts
|

Tax Buoyancy in the Caribbean: Evidence from Heterogenous Panel Cointegration Models

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of IDB's logo shall be subject to a separate written license agreement between the IDB and the user and is not authorized as part of this CC-IGO license.Following a peer review process, and with previous written consent by the Inter-American Development Bank (IDB), a revised vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The findings of our study arguably also suggest several policy implications for the Eastern Caribbean in the face of a damaging hurricane. Importantly, the region currently is faced with high public indebtedness and weak growth, a deterioration of the fiscal deficit (Khadan, 2019; Schipke et al, 2013; Schlotterbeck, 2017), and a tax system that accounts for more than four‐fifths of the total revenue (Schipke et al, 2013). Fiscal adjustment, in particular revenue mobilisation is therefore a main force shaping policies in these countries and is imperative for debt reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of our study arguably also suggest several policy implications for the Eastern Caribbean in the face of a damaging hurricane. Importantly, the region currently is faced with high public indebtedness and weak growth, a deterioration of the fiscal deficit (Khadan, 2019; Schipke et al, 2013; Schlotterbeck, 2017), and a tax system that accounts for more than four‐fifths of the total revenue (Schipke et al, 2013). Fiscal adjustment, in particular revenue mobilisation is therefore a main force shaping policies in these countries and is imperative for debt reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the region is identified as the most disaster‐prone region in the world on account of the frequent number of hurricane strikes, where the damage is equivalent to more than 2% of the affected country's gross domestic product (GDP) and can be expected every two and a half years (Rasmussen, 2004). Secondly, there is limited fiscal capacity in these islands as tax revenue accounts for only about 20% of GDP, with a relatively small nontax revenue of about 1% to 2% of GDP (Khadan, 2019Schipke et al, 2013). The countries' high degree of openness also makes customs taxes an attractive but falling source of revenue.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies that have examined tax elasticity in the world (Choudry 1979;Bruce et al 2004;Girouard and Andre, 2005;Cotton, 2012, Bunescu andComaniciu, 2013;Belinga et al 2014;Deli et al 2018;Khadan 2019). Bruce et al (2004) have investigated tax elasticity from 1967 to 2000 in the United States and results show that the elasticity for income taxes in the long-run is more than double that for sales taxes.…”
Section: Implications Of Tax Elasticitymentioning
confidence: 99%
“…Tagkalakis (2015) estimated the elasticity of corporate income tax revenue to output gap in Greece from 1993 to 2013, where results have shown that elasticity is about 1.40 to 1.55. have revealed that personal income tax and corporate income tax are not significant for economic growth in Serbia, but value added tax has significant effect to to GDP from 2006 to 2015. Khadan (2019) has examined tax buoyancy for a twelve Caribbean countries over the period 1991-2017. Findings of this research implie ЕКОНОМИКА ©Друштво економиста "Економика" Ниш http://www.ekonomika.org.rs that direct taxes have higher coefficients of elasticity compared to indirect taxes.…”
Section: Implications Of Tax Elasticitymentioning
confidence: 99%